Distributed Event-Triggered Formation Control of USVs with Prescribed Performance - Chen, Guangdeng; Yao, Deyin; Zhou, Qi; Li, Hongyi; Lu, Renquan (Journal of systems science and complexity, 2022)
In this paper, the formation control problem is investigated for a team of uncertain underactuated surface vessels (USVs) based on a directed graph. Considering the risk of collision and the limited communication range of USVs, the prescribed performance control (PPC) methodology is employed to ensure collision avoidance and connectivity maintenance. An event-triggered mechanism is designed to reasonably use the limited communication resources. Moreover, neural networks (NNs) and an auxiliary variable are constructed to deal with the problems of uncertain nonlinearities and underactuation, respectively. Then, an event-triggered formation control scheme is proposed to ensure that all signals of the closed-loop system are uniformly ultimately bounded (UUB). Finally, simulation results are presented to demonstrate the effectiveness of the proposed control scheme.